Die verskynsel van gesinne wat betrokke is by besluitneming oor onttrekking van lewensondersteunende behandeling - M. Oberholster; A. Gmeiner; M. Poggenpoel (AOSIS, 1998)
The overall objective of this study was to explore and describe the phenomenon of families who are involved in deciding about withdrawal of life-support treatment of a family member. A phenomenon analysis was undertaken in two phases. During the first phase, secondary analysis of primary data was done on the family used in Burger's study (1996:1-175) and was followed up by phenomenological interviews with families used as member checking from the same circumstances and according to the same criteria that Burger (1996:1 - 185) used in her study. Data were analysed in collaboration with an independent coder. The family used as member checking in this study is also used as data control. A literature control was conducted as part of data control. The themes that were identified included were: physical and bodily experiences of families; defence mechanisms used by families to cope with grief; emotional experiences of families; need of knowledge / perceptions / outlook on life / internal conflict / feelings of guilt/ ability to make decisions / respect of patient wishes / the effect of time and prior experiences; support needed by an given to families; spiritual and supernatural experiences / hope / acceptance / ability to 'let go' of the patient. In phase two, guidelines were described for psychiatric nurse specialists to mobilise resources for families to promote, maintain and restore their mental health as an integral part of health.